Otorhinolaryngologic Evaluation of Patients with Obstructive Sleep Apnea Syndrome in Tertiary Hospital of Nepal - Shrestha, Inku; Dhakal, Subodh; Acharya, Sudeep; Bista, Meera (Journal of Karnali Academy of Health Sciences, 2021)
Background: Obstructive sleep apnea is a global health problem characterized by repeated partial or complete obstruction of the upper airways during sleep accompanied by nocturnal hypoxemia, interruptions during sleep and sleepiness during daytime. It is commonly associated with road traffic accidents, diabetes mellitus and cardiovascular disease. The study was aimed to measure the different otorhinolaryngologic parameters of patients with obstructive sleep apnea and to compare these findings with different classes of polysomnography.Methods: A hospital based cross-sectional study was carried out among patient coming to department of Otorhinolaryngology of Kathmandu Medical College and Teaching Hospital. In total, 74 patients with obstructive sleep apnea participated in this study. Sociodemographic details, co-morbid illness and anthropometric measurements were recorded. Data was presented in the form of mean, standard deviation and percentage. Chi-square, student’s t-test were done using Statistical Package for the Social Sciences version 21. A p-value of